An Experimental Study on the Effect of a Water Injection System on Performance, Specific Fuel Consumption, and Exhaust Gas Emissions in a 110 cc Gasoline Engine - MARBUN, JALYIAMSEP; Mujahidin, Didin Mujahidin; Nashrul Chanief Hidayat (UIR PRESS, 2026)
ABSTRACT The increase in motor vehicle numbers in developing countries has led to higher fuel demand and increased exhaust emissions, requiring technologies to optimise combustion and reduce environmental impact. This study aims to evaluate the effects of injection systems on engine performance, fuel consumption, and exhaust emissions in 110 cc gasoline engines. The experiment compared two configurations: standard operation (STD) and water injection (H₂O), in which distilled water was sprayed at 15% of the fuel volume at 400 kPa, controlled by an Arduino-based PWM system. Exhaust emissions were measured using an HG-520 gas analyser; performance was tested on a dynamometer; and fuel consumption was evaluated through a 15 km road test. The results showed that water injection significantly reduced HC and CO emissions by 49.4% and 90%, respectively, while CO₂ remained stable and O₂ decreased by 74.60%, indicating more effective combustion. Engine performance improved, with power increasing by 6.26% and torque increasing by 6.26%. However, fuel consumption increased by 18.75%. Overall, water injection can improve combustion quality and engine output, but further optimisation is needed to improve fuel efficiency.